Evaluating threats to urban park ecosystems in megacities: a case study of effective environmental management strategies in Kyiv, Ukraine - Miroshnyk, Nataliia; Grabovska, Tetiana (Ecological Questions, 2025)
A systematic assessment of the park ecosystems environmental threats has not yet been conducted. To address this knowledge gap, we focused on assessing ecological threats to parks in megacities, exemplified by Kyiv, Ukraine, against the backdrop of rapid urbanization and climate change. As the world’s population increasingly resides in urban areas, the importance of parks as biodiversity hotspots and providers of ecosystem services becomes crucial. The aim of this research is to evaluate the ecological threats to park ecosystems in megacities, using the example of Kyiv, Ukraine, and explore possible links and long-term consequences of their impact. The research categorizes and evaluates 41 ecological threats, including salinization, war pollution, and desertification, impacting parks. A systematic approach combining integral analysis and expert assessments was employed in methodology. Findings reveal a complex interplay of threats, with physico-chemical impacts and pollution scoring highest in intensity and spatial distribution. The study highlights the need for adaptive management strategies, rapid threat assessments every 2-3 years, and collaboration with urban green space management authorities to safeguard biodiversity and ecosystem services amidst urban expansion and environmental challenges.